2015
DOI: 10.1186/s13034-015-0087-y
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about the risks for young people moving into, through and out of inpatient mental health care? Findings from an evidence synthesis

Abstract: BackgroundYoung people with complex or severe mental health needs sometimes require care and treatment in inpatient settings. There are risks for young people in this care context, and this study addressed the question: ‘What is known about the identification, assessment and management of risk in young people (aged 11–18) with complex mental health needs entering, using and exiting inpatient child and adolescent mental health services in the UK?’MethodsIn phase 1 a scoping search of two electronic databases (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Findings from a meta-analysis meta-analysis 72 Not available Corrigan et al (2012) [ 44 ] Challenging the public stigma of mental illness: A meta-analysis of outcome studies meta-analysis 72 Europe, North America, South America, Asia, Australia. Dalky (2012) [ 45 ] Mental illness stigma reduction interventions: Review of intervention trials quantitative systematic review with assessment of methodological quality 14 Not available de Mendonca Lima & Lopes (2012) [ 46 ] Systematic review on origin of stigma and discrimination against old persons with mental disorders integrative review 59 Not available Doley et al (2017) [ 47 ] Interventions to reduce the stigma of eating disorders: A systematic review and meta-analysis quantitative systematic review with no assessment of methodological quality and meta-analysis 18 Australia, US, UK, Indonesia Edwards et al (2015) [ 48 ] What do we know about the risks for young people moving into, through and out of inpatient mental health care? Findings from an evidence synthesis integrative review 40 USA, UK, Finland, Canada, Norway Ellison et al (2013) [ 49 ] Bipolar disorder and stigma: A systematic review of the literature integrative review 25 Public Stigma: UK, Germany, USA, Hong Kong, Malaysia, Canada, Japan, Singapore, Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from a meta-analysis meta-analysis 72 Not available Corrigan et al (2012) [ 44 ] Challenging the public stigma of mental illness: A meta-analysis of outcome studies meta-analysis 72 Europe, North America, South America, Asia, Australia. Dalky (2012) [ 45 ] Mental illness stigma reduction interventions: Review of intervention trials quantitative systematic review with assessment of methodological quality 14 Not available de Mendonca Lima & Lopes (2012) [ 46 ] Systematic review on origin of stigma and discrimination against old persons with mental disorders integrative review 59 Not available Doley et al (2017) [ 47 ] Interventions to reduce the stigma of eating disorders: A systematic review and meta-analysis quantitative systematic review with no assessment of methodological quality and meta-analysis 18 Australia, US, UK, Indonesia Edwards et al (2015) [ 48 ] What do we know about the risks for young people moving into, through and out of inpatient mental health care? Findings from an evidence synthesis integrative review 40 USA, UK, Finland, Canada, Norway Ellison et al (2013) [ 49 ] Bipolar disorder and stigma: A systematic review of the literature integrative review 25 Public Stigma: UK, Germany, USA, Hong Kong, Malaysia, Canada, Japan, Singapore, Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“… Four events. No information provided No information provided Edwards et al [ 43 ] Individual interviews—aimed at identifying topics for review to focus on. Meeting—descriptive maps from initial scoping review/mapping exercise were presented.…”
Section: Resultsmentioning
confidence: 99%
“…Patients reported stepping in when staff had not noticed or were not available to meet the needs of their peers on the ward but also reported intrusive aspects of peer relationships on the ward. Similarly, an evidence synthesis by Edwards et al (2015) found that alongside positive experiences of inpatient peer relationships, young people spoke about negative aspects of living with people with mental health difficulties, alongside ambivalence and fear. It is thus possible that negative aspects of patient encounters on the locked ward may not have been not fully observed or attended to by staff, and that this alongside generally less intensive staff support may have led to staff overestimating the TH of the locked rehabilitation ward.…”
Section: Discussionmentioning
confidence: 99%